Meningkatkan Literasi Digital Melalui Pelatihan Canva AI pada Guru dan Edukasi Keamanan Digital bagi Siswa Sekolah Dasar - Khaeruddin, Muhammad (VIDHEAS: Jurnal Nasional Abdimas Multidisiplin, 2025)
Digital transformation in the education sector requires the improvement of digital literacy among teachers and students at the elementary school level. One of the main challenges faced is the limited use of educational technology by teachers and the low awareness of students regarding online safety and ethical behavior in digital environments. This article aims to describe the implementation of a community service program conducted through the Kuliah Kerja Nyata (KKN) of Universitas Bhayangkara Jakarta Raya, which focused on Canva AI training for teachers and digital literacy as well as cyber safety education for students at MI Plus Roudhotul Muhibbin Bekasi (RMB). The research method employed was a descriptive qualitative approach using observation, participation, documentation, and simple assessment techniques. The results indicate an improvement in teachers’ ability to create visual learning media using Canva AI and an increase in students’ understanding of evaluating digital information, identifying fake news, and applying cyber safety practices. This program proves to be effective as a model for enhancing digital literacy in elementary schools through the integration of AI-based technology.